Traffic Safety 2016
DOI: 10.1136/injuryprev-2016-042156.530
|View full text |Cite
|
Sign up to set email alerts
|

530 Road crashes in metro manila: overview of road safety

Abstract: BackgroundRoad crashes is one of the highest cause of morbidity and fatality in the Philippines.The study tried to look into the trends of fatal and non-fatal injuries due to road crashes in Metro Manila Philippines, including all other relevant factors such as damage to property, number of registered cars, and time of accident.MethodsThe study looked at all raw data and databases coming from all agencies that generate traffic and road safety monitoring and evaluation. These are the Metro manila Development Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a study in Pakistan, severe injuries were attributed to poor usage of helmets and speeding. 11 Lu (2016) 6 in a study in Philippines and Ashraf et al (2019) 40 in South Korea both found that the increasing car registrations could also be a contributing factor for the increased road accidents due to road congestion. It is also evident that there are more private vehicles registered than vehicles for hire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Pakistan, severe injuries were attributed to poor usage of helmets and speeding. 11 Lu (2016) 6 in a study in Philippines and Ashraf et al (2019) 40 in South Korea both found that the increasing car registrations could also be a contributing factor for the increased road accidents due to road congestion. It is also evident that there are more private vehicles registered than vehicles for hire.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Land of Transportation Office showed that there was an average increase of 10.56% in the number of registered vehicles from 2017 to 2019. 5 Lu (2016) 6 associated the increase in car registrations and road congestion to a higher risk for road traffic accidents. The findings of this study are similar to India wherein an observed trend in increasing road traffic accidents from 2005 to 2015 was attributed to increasing vehicles on the Highly significant association road.…”
Section: Discussionmentioning
confidence: 99%
“…16 In Poland and Metro Manila, the increase in car registrations leads to congestions on the road. 17,18 A report in Davao City showed that although 80% of road users are private car owners, the usage of cars in the roadways in the area is low. 19 Nevertheless, it cannot be overlooked that there has been an observed increase in Davao's annual average daily traffic (AADT) trend.…”
Section: Discussionmentioning
confidence: 99%
“…7 This may be related to the consistently increasing number of registered vehicles from 2010 to 2018, leading to congestion of roads in Metro Manila, thereby increasing the risk of road crashes. 7,16 The highest number of road crash admissions from Metro Manila was seen in 2016.…”
Section: Date Of Injurymentioning
confidence: 99%